Application of 3 in 1 Pentol Printing Machine Technology at the Pentol Traders Association in TulungagungPenerapan Teknologi Mesin Pencetak Pentol 3 In 1 Pada Paguyuban Pedagang Pentol Kabupaten Tulungagung - Nadliroh, Kuni; Mahmudi, Haris; Fauzi, Ah. Sulhan; Ilham, M. Muslimin; Huda, Miftahul (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Pentol is one of the most popular snacks, from children to adults and even to old age. In terms of making pentol, it is a snack that requires a long process. Starting from grinding the meat, mixing it with spices and flour and the last is the pentol printing process. In general, pentol traders grind their meat in the market, namely at a public meat mill, but the mill is only open Monday to Saturday and holidays on Sundays. Apart from that, there are only two meat grinding places for pentol in the Rejotangan area, namely the the first is at Pasar Rejotangan and the second is at Pasar Panjerejo, the distance between the two mills is quite far, which is about 6 km so a long queue is needed to grind it, besides that it takes a long time to print pentols, it takes 2 hours to print 5 kg of dough dough. . This is a major problem in the pentol making process. To overcome this, a tool has been designed that can be used to make pentols, starting from grinding meat, mixing meat, and printing. So that this tool will ease and speed up the process of making pentol for pentol traders. The dedication activity was carried out for 1 year, while the handover of the tools was carried out on Wednesday December 14, 2022 at the house of a member of the pentol traders association.